Quadriceps strength, patellar tendon quality, relative load exposure, and knee symptoms in male athletes before the anterior cruciate ligament reconstruction - Pereira, Carla S.; Klauznicer, Jasenko; Maree, Dustin; McAuliffe, Sean; Farooq, Abdulaziz; Whiteley, Rod; Finni, Taija (Frontiers in Rehabilitation Sciences, 2023)
Introduction Anterior cruciate ligament (ACL) injuries cause knee instability, knee pain, weight-bearing adjustments, and functional deficits but their association to patellar tendon quality is unknown. Our purpose was to investigate quadriceps strength, patellar tendon quality, relative load exposure, perceived knee stability, knee pain, extension angle, and time from ACL injury; in addition to examining their relative associations. Methods Injured and uninjured legs of 81 male athletes of different sports with a unilateral ACL injury (18–45 years) were examined. Participants reported location and intensity of knee pain and their perceived stability using a numerical rating scale (NRS 0–10). Strength was tested with an isokinetic device. Tendon quality was measured using ultrasound tissue characterization. Means ± standard deviation (SD) of perceived knee stability, knee extension angle, knee pain, isokinetic quadriceps strength in relation to body mass, proportion of echo-types (I–IV), tendon volume, and number of days from ACL injury to assessment are reported. Values of effect sizes (ES) and correlations (rs) were calculated. Results ACL injured leg demonstrated reduced reported knee stability (6.3 ± 2.5), decreased knee extension angle (−0.7 ± 3.1° vs. −2.7 ± 2.2°; ES = 0.7; P < 0.001), greater knee pain (NRS 3.1 ± 2.2 vs. 0.0 ± 0.1; ES = 2.0; P < 0.001), and 22% lower quadriceps strength (228.0 ± 65.0 vs. 291.2 ± 52.9 Nm/kg: ES = 1.2; P < 0.001) as compared to the uninjured leg. However, patellar tendons in both legs displayed similar quality. Quadriceps strength was associated with stability (rs = −0.54; P < 0.001), pain (rs = −0.47; P < 0.001), extension angle (rs = −0.39; P < 0.001), and relative load exposure (rs = −0.34; P < 0.004). Echo-types distribution was beneficially associated with time from ACL injury (rs range: −0.20/ −0.32; P < 0.05). Discussion ACL injured athletes displayed knee pain, extension deficit, and weaker quadriceps in the injured leg. While there were no differences in patellar tendon quality between legs, longer time from ACL injury showed better tendon quality.